1983
DOI: 10.1246/cl.1983.913
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Optically Active Phosphine Oxides by Regioselective Cleavage of Cyclic Phenylphosphonite With Alkyl Halides

Abstract: The Arbuzov reaction of (2S,4S)-4-methyl-2-phenyl-1,3,2-dioxaphosphorinane with various alkyl halides gave the diastereomerically pure phosphinates with regioselective cleavage of the primary carbon–oxygen bond. These phosphinates reacted with Grignard reagents to give optically active phosphine oxides in high optical yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…(33) The Michaelis-Arbuzov reaction is one of the most universal methods for the formation of carbon-phosphorus bonds. The classical Michaelis-Arbuzov reaction consists in the alkylation of trivalent phosphorus acid esters with alkyl halides to form derivatives of the corresponding pentavalent phosphorus acids containing a new P-C bond: phosphonates, phosphinates or tertiary phosphine oxides (Equation 34) [49][50][51][52][53][54]. The stereochemistry of this reaction is of particular interest, the research results of which have not been fully generalized, although intensive studies were carried out.…”
Section: (28)mentioning
confidence: 99%
See 2 more Smart Citations
“…(33) The Michaelis-Arbuzov reaction is one of the most universal methods for the formation of carbon-phosphorus bonds. The classical Michaelis-Arbuzov reaction consists in the alkylation of trivalent phosphorus acid esters with alkyl halides to form derivatives of the corresponding pentavalent phosphorus acids containing a new P-C bond: phosphonates, phosphinates or tertiary phosphine oxides (Equation 34) [49][50][51][52][53][54]. The stereochemistry of this reaction is of particular interest, the research results of which have not been fully generalized, although intensive studies were carried out.…”
Section: (28)mentioning
confidence: 99%
“…37Stereochemical studies of the Michaelis-Arbuzov reaction of dioxaphospholane with alkyl halides, performed by Michalski et al, showed the evidence for equilibrium between phosphorane and phosphonium intermediates as shown in Equations (38) and 39 The asymmetric version of the Michaelis-Arbuzov reaction was investigated by several authors. For example, it was found that the cyclic phenylphosphonite obtained from (S)-1,3-butanediol reacts with alkyl halides with ring opening through cleavage of the P-O bonds and the formation of an acyclic product (Equation (40)) [52]. 40The reaction of diastereomerically pure (2R,4S,5R)-3,4-dimethyl-2,5-diphenyl-1,3,2oxazaphospholidine with alkyl halides led to the formation of diastereomeres of the phosphonium salt in the ratio 85:15 (de 70%).…”
Section: (28)mentioning
confidence: 99%
See 1 more Smart Citation
“…Among a few protocols leading to optically active phosphine oxides and phosphinates based on asymmetric synthesis which have been worked-up [10][11][12][13][14][15][16][17][18][19] since the classical works of Mislow et al [20][21] one can apply an approach proposed by Juge based on a Arbusov rearrangement of diasteromerically pure 2-phenyl-1,3,2-oxazaphospholidine (2R,4S, 5R)-3 which was prepared by the reaction of achiral bis-(diethylamino)phenylphosphine 1 with L-ephedrine 2 (Scheme 1) [22]. Its reaction with alkyl halides gave the phosphinamides 4a-d by the Arbusov rearrangement with retention of configuration at the phosphorus atom and stereoselectivity which depends on the steric requirements of the alkyl group and reaction conditions (de from 0 to 85%).…”
Section: The Preparation Of Enantiomerically (Di-astereomerically) Pumentioning
confidence: 99%
“…An example is provided by the work of Segi et al (212). An example is provided by the work of Segi et al (212).…”
Section: Asymmetric Syntheses Using Cyclic Covalent Diastereomersmentioning
confidence: 99%